PENGGUNAAN MEDIA PUZZLE DAN TUBOPIN UNTUK MENINGKATKAN PEMAHAMAN KONSEP BANGUN DATAR PADA KELAS IV SEKOLAH DASAR - Akmal, Arina Zawani; Manurung, Asrar Aspia; Irvan, Irvan; Simare-mare, Lydia Doris Fransiska (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
This study aims to improve the understanding of flat shape concepts among fourth-grade students at SD Negeri 065853 Medan through the use of Puzzle and Tubopin media. The research method used is Classroom Action Research (CAR), consisting of two cycles. Each cycle includes the stage of planning, implementation, observation, and reflection. The research instruments include observation, tests, and documentation. The results of the study indicate an improvement in students’ conceptual understanding, with the average score increasing from 55.50 in the pre-cycle to 78.75 in the second cycle. The percentage of students meeting the Minimum Mastery Criteria (KKM) also increased from 30% to 85%. This proves that the use of Puzzle and Tubopin media is effective in making the learning process more enjoyable, interactive, and meaningful.